HAMBATAN-HAMBATAN DALAM MENGEMBANGKAN KECERDASAN LOGICAL/MATHEMATICAL PADA PEMBELAJARAN TERPADU MODEL WEBBED BERBASIS KECERDASAN JAMAK DI TKIT SALMAN AL FARISI II YOGYAKARTA(Studi Eksplorasi) - Caturiyati, Caturiyati; Hidayati, Kana; Lestari, Himmawati Puji (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2007)
One of the important intelligent component for children’s future and need to be developing early is logical/mathematical intelligent. Integrated learning is carried out in learning process that integrates sistematically and holistically the effort of developing child. One of the integrated learning model is webbed model, a learning model that integrates learning and developing for children in a topic that covers some subjects. TKIT Salman Al Farisi II applies learning with themes where those themes become a learning guide in class. It needs to investigate the constraints in optimizing of developing child’s logical/mathematical intelligent by integrated learning in TKIT Salman Al Farisi II. The results of this exploration research indicates that there are some constraints in developing child’s logical/mathematical intelligent. They are limited class room, limited facility, i.e. computer, children’s mood varying according to healthy and environment condition and different children’s ability.Key words : constraint, logical/mathematical intelligent, webbed model.